Necrotic Myocardial Cells Release Damage‐Associated Molecular Patterns That Provoke Fibroblast Activation In Vitro and Trigger Myocardial Inflammation and Fibrosis In Vivo. Issue 6 (June 2015) - Zhang, Weili; Lavine, Kory J.; Epelman, Slava; Evans, Sarah A.; Weinheimer, Carla J.; Barger, Philip M.; Mann, Douglas L.
Abstract : Background: Tissue injury triggers inflammatory responses that promote tissue fibrosis; however, the mechanisms that couple tissue injury, inflammation, and fibroblast activation are not known. Given that dying cells release proinflammatory "damage‐associated molecular patterns" (DAMPs), we asked whether proteins released by necrotic myocardial cells (NMCs) were sufficient to activate fibroblasts in vitro by examining fibroblast activation after stimulation with proteins released by necrotic myocardial tissue, as well as in vivo by injecting proteins released by necrotic myocardial tissue into the hearts of mice and determining the extent of myocardial inflammation and fibrosis at 72 hours. Methods and Results: The freeze–thaw technique was used to induce myocardial necrosis in freshly excised mouse hearts. Supernatants from NMCs contained multiple DAMPs, including high mobility group box‐1 (HMGB1), galectin‐3, S100β, S100A8, S100A9, and interleukin‐1α. NMCs provoked a significant increase in fibroblast proliferation, α–smooth muscle actin activation, and collagen 1A1 and 3A1 mRNA expression and significantly increased fibroblast motility in a cell‐wounding assay in a Toll‐like receptor 4 (TLR4)‐ and receptor for advanced glycation end products–dependent manner. NMC stimulation resulted in a significant 3‐ to 4‐fold activation of Akt and Erk, whereas pretreatment with Akt (A6730) and Erk (U0126) inhibitors decreased NMC‐induced fibroblast proliferation dose‐dependently. The effects of NMCs on cell proliferation and collagen gene expression were mimicked by several recombinant DAMPs, including HMGB1 and galectin‐3. Moreover, immunodepletion of HMGB1 in NMC supernatants abrogated NMC‐induced cell proliferation. Finally, injection of NMC supernatants or recombinant HMGB1 into the heart provoked increased myocardial inflammation and fibrosis in wild‐type mice but not in TLR4‐deficient mice. Conclusions: These studies constitute the initial demonstration that DAMPs released by NMCs induce fibroblast activation in vitro, as well as myocardial inflammation and fibrosis in vivo, at least in part, through TLR4‐dependent signaling.